Personal fitness training services to improve health outcomes: A survey exploring clients' perspectives - Čurović Ivan; Grečić David (Fizička Kultura)
It is currently unclear how personal fitness training (PT) clients in Serbia evaluate this service and what motivates them to be consistent with the training practice in the quest for obtaining physical literacy and health outcomes. A cross-sectional explorative study was used to investigate consumers' perceptions on the PT service with the aim to inform trainers on clients' motivational factors, challenges and experiences in the pursuit of training goals. A total of 148 respondents completed the anonymous questionnaire via Qualtrics platform. The key findings of the study can be summarised as follows: 1) PT clients in Serbia are using up these services primarily for sustained exercise adherence and motivation to attain and maintain health-related goals, 2) PT clients in Serbia highly value professional dedication of a personal trainer as well as their ability to facilitate supportive social environment, 3) Personal trainers in Serbia are expected to play a significant role in motivating clients, especially those with weight management needs and limited capacity for self-directed lifestyle changes. Additionally, there is a need for increased transparency from fitness centres regarding the qualifications of employed trainers and their backgrounds. Stakeholders should find a way to encourage PT consumers to provide feedback and express their impressions more effectively, thereby reducing the chances of losing the motivation to hire or keep a personal trainer. In conclusion, PT clients in Serbia value holistic training practices and expect their personal trainers to lead them and motivate them to reach the targeted health-related objectives.